Program Pengabdian Masyarakat Dengan Skrining Urin Dan Edukasi Kesehatan Untuk Pencegahan Infeksi Saluran Kemih - Mano, Donatila; Waltoni, Bobby Marshel Ancheloti; Mayello, Stanislas Kotska Marvel (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
Urinary tract infection (UTI) is a medical condition caused by a bacterial infection of the urinary system. In the elderly, urinary tract infections can occur without obvious symptoms, so screening for urinary tract infections is needed for early detection and appropriate management. Education is also needed regarding risk factors, such as urinary retention habits and personal hygiene, so that the risk of infection can be reduced. This activity is carried out using the PDCA (Plan-Do-Check-Act) method, so it is hoped that it can increase effectiveness in preventing UTIs. This activity is carried out with the aim of maintaining and improving the quality of life of the elderly, especially in preventing urinary tract infections through early detection and healthy lifestyle changes. Keywords: Education, Elderly, Urinary tract infections, Urin examination